The Role of Brand Equity, Brand Authenticity, Brand Trust to Increase Customer Satisfaction - Panyekar, Anindya; Marsasi, Endy Gunanto (Universitas Hamzanwadi, 2024)
This study aims to analyze the effect of the relationship between brand experience, brand authenticity, brand equity, brand trust, and customer satisfaction in Generation Y and Z shoe footwear. This study uses a quantitative approach method using a purposive sampling technique, resulting in 177 samples supported by structural Equation Modeling (SEM) and analyzed through AMOS Graphics 24 software. The results of the analysis show that brand authenticity has a significant negative effect on customer satisfaction. Brand experience on brand authenticity has a significant positive impact. Brand experience and relationships have a significant positive effect on customer satisfaction. The relationship between brand experience has a significant positive effect on brand equity. The impact of brand authenticity on brand trust has a significant positive effect. The relationship between brand authenticity and customer satisfaction directly impacts customer satisfaction because it has a significant negative effect, meaning that brand authenticity can have a positive and negative impact based on customer satisfaction.